The effect of an acute bout of exercise on executive function among individuals with schizophrenia. (30th December 2016) - Subramaniapillai, Mehala; Tremblay, Luc; Grassmann, Viviane; Remington, Gary; Faulkner, Guy
Abstract: Cognitive impairment represents a significant source of disability among individuals with schizophrenia. Therefore, the aim of this study was to investigate, at a proof-of-concept level, whether one single bout of exercise can improve executive function among these individuals. In this within-participant, counterbalanced experiment, participants with schizophrenia ( n =36) completed two sessions (cycling at moderate-intensity and passively sitting) for 20 min, with a one-week washout period between the two sessions. Participants completed the Wisconsin Card Sorting Test (WCST) before and after each session to measure changes in executive function. The inclusion of both sessions completed by each participant in the analyses revealed a significant carryover effect. Consequently, only the WCST scores from the first session completed by each participant was analyzed. There was a significant time by session interaction effect for non-perseverative errors. Post-hoc Tukey's HSD contrasts revealed a significant reduction in non-perseverative errors in the exercise group that was of moderate-to-large effect. Furthermore, there was also a moderate between-group difference at post-testing. Therefore, an acute bout of exercise can improve performance on an executive function task in individuals with schizophrenia. Specifically, the reduction in non-perseverative errors on the WCST may reflect improved attention, inhibition and overall working memory. Highlights: One bout of aerobic exercise can produce immediate improvements in cognition. Changes appear to be strongest in attention, inhibition and working memory. Exercise may be a feasible strategy to acutely improve cognition in schizophrenia.